Effect of LRRK2 G2385R Variant on Subthalamic Deep Brain Stimulation Efficacy in Parkinson's Disease in a Han Chinese Population - Chen, Si; Liu, Hong; Wu, Qian-qian; Xu, Shu-jun; Li, Wei-guo; Chen, Teng; Li, Chao; Ma, Xiang-yu; Xu, Shuo; Liu, Yi-ming (Frontiers in Neurology, 2019)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an effective treatment for advanced Parkinson’s disease (PD). The G2385R variant of LRRK2 is a risk factor for PD in Han Chinese individuals. We retrospectively compared the clinical outcomes of STN-DBS surgery between PD Han Chinese G2385R variant carriers and non-carriers. Fifty-seven PD patients with bilateral STN-DBS were enrolled, including 8 G2385R+ variant carriers (G2385R+ group) and 49 non-carriers (G2385R- group). Clinical data included Unified Parkinson’s Disease Rating Scale (UPDRS) parts I to IV, levodopa equivalent daily dose (LEDD), Mini-Mental State Examination Scale (MMSE) score, and Hamilton Depression Rating Scale (HAMD) score measured prior to DBS and 12 months post-DBS. DBS settings were also recorded. All PD patients benefited from STN-DBS surgery. There were no statistical differences between the two groups in terms of motor function, daily living activities, and LEDD reductions at 12 months post-DBS. The rigidity of the post-surgical G2385R+ group was significantly improved compared with that of the G2385R- group (P=0.045). Post-surgical voltage in the G2385R+ group was significantly higher than that in the G2385R- group (P=0.033). STN-DBS outcomes were not influenced by the LRRK2 G2385R variant in Han Chinese patients.